On property rights and incentives in academic publishing - Pitsoulis, Athanassios; Schnellenbach, Jan (Research policy, 2012)
The peer review system in academic publishing performs two important functions by screening a manuscript for its quality, and by helping to further improve an author’s work. However, it often fails to perform these functions in a satisfactory manner. We argue that property rights theory can be fruitfully applied to understand these shortcomings, and to develop reform proposals. The present paper discusses the incentive-problems in journal peer review from an institutional economics perspective, arguing that the incentives of both authors and reviewers to fully exploit a manuscript’s potential depend on their property rights. Based on this theory of peer review, we argue that the recent proposal of an “as is” review policy combined with increased accountability of referees can be expected to result in a higher efﬁciency of peer review.